2020
DOI: 10.1038/s41396-020-00775-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals insights into cyanobacterial evolution and habitat adaptation

Abstract: Cyanobacteria are photosynthetic prokaryotes that inhabit diverse aquatic and terrestrial environments. However, the evolutionary mechanisms involved in the cyanobacterial habitat adaptation remain poorly understood. Here, based on phylogenetic and comparative genomic analyses of 650 cyanobacterial genomes, we investigated the genetic basis of cyanobacterial habitat adaptation (marine, freshwater, and terrestrial). We show: (1) the expansion of gene families is a common strategy whereby terrestrial cyanobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 79 publications
10
109
0
Order By: Relevance
“… Chen et al (2020) also noted that differences in horizontal gene transfer (HGT) are related to genome size, with smaller genomes showing less HGT and larger genomes having a greater HGT probability. They also found that hot spring cyanobacteria specifically have smaller genome sizes and less HGT into the genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Chen et al (2020) also noted that differences in horizontal gene transfer (HGT) are related to genome size, with smaller genomes showing less HGT and larger genomes having a greater HGT probability. They also found that hot spring cyanobacteria specifically have smaller genome sizes and less HGT into the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Since all Thermosynechococcus in this study are found in hot springs -which typically have reduced microbial diversity in comparison to other environments such as soils (Ward et al, 1998)-the conserved core and small pangenome of the Thermosynechococcus genus may reflect a more limited opportunity for lateral gene transfer, which in turn could lead to less opportunity for lateral gene transfer and smaller genomes. Chen et al (2020) also noted that differences in horizontal gene transfer (HGT) are related to genome size, with smaller genomes showing less HGT and larger genomes having a greater HGT probability. They also found that hot spring cyanobacteria specifically have smaller genome sizes and less HGT into the genome.…”
Section: Genus and Family Level Comparison Of The Genus Thermosynechococcus And The Family Thermosynochococcaceaementioning
confidence: 99%
“…Nostocales; Zamocky et al., 2012). Synechococcus PCC 7002 lacks Mn 2+ ‐catalase, which is widespread in terrestrial cyanobacteria (Ballal et al., 2020; Banerjee et al., 2012; Bihani et al., 2016; Chakravarty et al., 2016; Chen et al., 2020; Table S1) and was likely present in early cyanobacterial lineages (Klotz & Loewen, 2003; Zamocky et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nostocales; Zamocky et al, 2012). Synechococcus PCC 7002 lacks Mn 2+ -catalase, which is widespread in terrestrial cyanobacteria (Ballal et al, 2020; Banerjee et al, 2012; Bihani et al, 2016; Chakravarty et al, 2016; Chen et al, 2020) (Table S1) and was likely present in early cyanobacterial lineages (Klotz and Loewen, 2003; Zamocky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%